Ni incorporation in MgFe2O4 for improved CO2-splitting activity during solar fuel production - Gorakshnath Takalkar (14151135) (2020)
Efficacy of the sol–gel derived Ni-doped Mg-ferrites for an enhanced CO2 splitting activity is investigated. The results allied with the characterization indicate the formation of nominally phase pure Ni-doped Mg-ferrites with a coarser particle morphology. Ni-doped Mg-ferrites are further tested for multiple thermal reduction as well as CO2 splitting steps by using a thermogravimetric analyzer. The results associated with the thermogravimetric analysis confirmed that most of the Ni-doped Mg-ferrites attained a steady TR aptitude after crossing the 5th or 6th cycle. Likewise, the CS capability of all the Ni-doped Mg-ferrites accomplished consistency after 4th cycle (except for Ni0.11Mg0.88Fe2.01O4.005). The Ni0.90Mg0.11Fe2.04O4.070 showed the highest amount of O2 release (117.1 μmol/g cycle) and CO production (210.3 μmol/g cycle) in ten consecutive thermochemical cycles. Besides, Ni0.29Mg0.72Fe1.98O3.980 indicated better re-oxidation aptitude (nCO/nO2 ratio = 1.89) when compared with other Ni-doped Mg-ferrites. Other Information Published in: Journal of Materials Science License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10853-020-04794-1